Fascism and Sinarquismo: Popular Nationalisms against the Mexican Revolution - Michaels, Albert L. (A journal of church and state, 1966)
Albert L. Michaels; Fascism and Sinarquismo: Popular Nationalisms against the Mexican Revolution, Journal of Church and State, Volume 8, Issue 2, 1 March 1966,